2003
DOI: 10.1074/jbc.m310014200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of GCP16, a Novel Acylated Golgi Protein That Interacts with GCP170

Abstract: GCP170, a member of the golgin family associated with the cytoplasmic face of the Golgi membrane, was found to have a Golgi localization signal at the NH 2 -terminal region (positions 137-237). Using this domain as bait in the yeast two-hybrid screening system, we identified a novel protein that interacted with GCP170. The 2.0-kilobase mRNA encoding a 137-amino acid protein of 16 kDa designated GCP16 was ubiquitously expressed. Immunofluorescence microscopy showed that GCP16 was co-localized with GCP170 and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
5
44
1
Order By: Relevance
“…GCP16 is a 137-amino acid protein with no obvious structural features other than a short predicted coiled-coil domain. Ohta et al (25) found that GCP16 is palmitoylated and that fatty acylation accounts for the behavior of GCP16 as an integral membrane protein and its association with the Golgi complex. Overexpression of GCP16 in COS cells impaired trafficking of vesicular stomatitis virus glycoprotein to the cell surface and modestly inhibited secretion of a soluble form of dipeptidyl peptidase IV without having an obvious effect on Golgi morphology (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GCP16 is a 137-amino acid protein with no obvious structural features other than a short predicted coiled-coil domain. Ohta et al (25) found that GCP16 is palmitoylated and that fatty acylation accounts for the behavior of GCP16 as an integral membrane protein and its association with the Golgi complex. Overexpression of GCP16 in COS cells impaired trafficking of vesicular stomatitis virus glycoprotein to the cell surface and modestly inhibited secretion of a soluble form of dipeptidyl peptidase IV without having an obvious effect on Golgi morphology (25).…”
Section: Discussionmentioning
confidence: 99%
“…GCP16 was previously identified as a palmitoylated protein that interacts with the Golgi autoantigen GCP170 (25). GCP170 is a member of the golgin family, high molecular weight proteins with cytoplasmic coiled-coil domains that are localized to the cytoplasmic face of the Golgi cisternae (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent elegant fluorescence experiments revealed that depalmitoylated H-and N-Ras rapidly traffic from the cell surface to the Golgi via a non-vesicular pathway [64,65]. The palmitoyltransferase complex responsible for palmitoylating Ras was recent identified as DHHC9/GCP16 (Erf2/Erf4 in yeast) and these have also been localised to the Golgi [66][67][68]. Taken together these data suggest a model where palmitoylation in the Golgi stabilises Ras-membrane interactions facilitating trafficking to the plasma membrane before depalmitoylation causes Ras to become cytosolic and traffic back to the ER/Golgi.…”
Section: Compartmentalisation Of Rasmentioning
confidence: 99%